Nasosinus mucoceles: about 13 cases in Donka University Hospital, Republic of Guinea - Keita, Abdoulaye; Diallo, Ibrahima; Diallo, Mamadou A.; Kourouma, Sayon; Diallo, Mamadou M. R.; Fofana, Mamady; Diallo, Mamadou M.; Kaman, Mohamed C. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Nasosinus mucoceles are expansive pseudocystic formations of the sinuses of the face formed by chronic retention of mucus in a sinus cavity due to ostial obstruction. Methods: This was a descriptive study of retrospective data collection. It was carried out over ten years (from 01 January 2008 to 01 January 2018) at the otorhinolaryngology and head and neck surgery department of the Donka University Hospital. Results: We found an incidence of 1.3 cases per year. The average age was 39.77 years with extremes of 10 years and 60 years. The sex ratio was 0.6. Headaches (92.3%) and facial swelling (76.9%) were the main reasons for consultation. The ethmoid-frontal form was predominant (53.8%). CT scan of the sinuses was performed in all patients. Magnetic resonance imaging was not performed. The diagnosis of certainty was made by anatomy pathology (100%). The paralateral nasal route was the main approach (46.2%). The simple postoperative follow-ups were simple (100%). Lethality was zero. Conclusions: We noted a low incidence of naso-sinus mucoceles in our series. The symptomatology was fairly standard. Imagery and anatomy pathology established the diagnosis. However, endonasal surgery has become essential in the management. Simple postoperative follow-up would be related to the experience of the surgeon, the severity of the lesions and the proper conduct of post-operative care.